Faktor-Faktor Keputusan Wisatawan Mengunjungi Destinasi Wisata Spiritual: Kasus Gua Maria Kerep Ambarawa - Reagan Brian; Johannes Kurniawan (Pusaka: Journal of Tourism, Hospitality, Travel and Business Event, 2023)
Spiritual tourism is a form of tourism where one of the objectives is to seek peace of mind and spirituality. Spiritual tourism has been around for a long time, but recently it has experienced an increasing trend with many young people needing a break from their routine and seeking spiritual peace. There are various choices of spiritual tourism destinations, but there are still few studies that find out the background of tourists' decision making to visit. This study was conducted to try to find out this. This study uses two price and attractiveness variables as the antecedent variables of the decision to visit. The study was carried out by distributing questionnaires to tourists taking spiritual tourism trips to St. Mary Grotto Kerep Ambarawa. The results of the questionnaire were then processed using multiple linear regression methods. The results of the study show that both price and attractiveness have an influence on tourists' visiting decisions to a spiritual tourism destination.